2012
DOI: 10.3233/nre-2012-0746
|View full text |Cite
|
Sign up to set email alerts
|

Empowering preadolescents with ABI through metacognition: Preliminary results of a randomized clinical trial

Abstract: The aim of this randomized clinical trial study was to evaluate the efficacy of an intervention program based on social mediation, cooperative learning and metacognition (Metacognitive Dimension) in preadolescents with acquired brain injury (ABI). Participants/Methods: Participants were 29 ABI preadolescents: 14 in the experimental group and 15 in the control group (average age, 10.4 y.o.; average time of lesion, 5.3 years). Evaluations were conducted 3 months after the start of the intervention, using the Eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 11 publications
1
14
0
1
Order By: Relevance
“…A total of 11 examined full texts met all eligibility criteria. The authors specifically want to remark on the exclusion of studies into familycentred interventions (see for example (27)(28)(29)(30)(31)) and on a peer-supported metacognition intervention (32). While these studies examine cognitive functioning as one of their primary outcome measures, the interventions themselves were mainly focused on finding the best intervention context (i.e.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 11 examined full texts met all eligibility criteria. The authors specifically want to remark on the exclusion of studies into familycentred interventions (see for example (27)(28)(29)(30)(31)) and on a peer-supported metacognition intervention (32). While these studies examine cognitive functioning as one of their primary outcome measures, the interventions themselves were mainly focused on finding the best intervention context (i.e.…”
Section: Study Selectionmentioning
confidence: 99%
“…While these studies examine cognitive functioning as one of their primary outcome measures, the interventions themselves were mainly focused on finding the best intervention context (i.e. familycentred or clinician delivered) (27), or were directed at family problem-solving and communication (28)(29)(30)(31) or cooperative learning and social mediation (32). While these studies give a good indication that family and/or peer involvement can be beneficial for rehabilitation after paediatric ABI, it would not be clear whether an effect of the intervention would have been the result of the intervention itself or of the system involved.…”
Section: Study Selectionmentioning
confidence: 99%
“…5 The results suggest that children with ABI require more than authoritative parenting practices to improve self-regulation. Braga et al 68 and Chan and Fong 69 found improvements in self-regulation after an intervention in which participants learned metacognitive and problem-solving strategies. These interventions were applied directly to the children in face-toface group sessions that took place twice a week.…”
Section: Disruptive Behavior At Schoolmentioning
confidence: 99%
“…These interventions were applied directly to the children in face-toface group sessions that took place twice a week. 68,69 Poor self-regulation in childhood is a predictor of a variety of mental health problems in adulthood. 8 Hence, it is important to find effective interventions to improve emotional, cognitive, and behavioral self-regulation in children with ABI.…”
Section: Disruptive Behavior At Schoolmentioning
confidence: 99%
See 1 more Smart Citation